2015
DOI: 10.3141/2520-15
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Bike Lane Buffer Types on Perceived Comfort and Safety of Bicyclists and Potential Bicyclists

Abstract: Buffered and protected bike lanes are increasingly recognized as a valuable tool in enticing potential or wary cyclists to use a bicycle for transportation. These facilities—which provide extra space and (in the case of protected bike lanes) physical separation from motor vehicles—have been studied and are preferred by many bicyclists over traditional bike lanes. There has been little research, however, on the difference between buffer types and how they affect people's sense of the safety and comfort of bicyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 13 publications
2
28
0
Order By: Relevance
“…Other types of infrastructure, such as sharrows and bicycle signs, may be insufficient to influence bicycling behavior in a meaningful way. Research suggests that protected bicycle lanes are perceived as the most safe and comfortable type of bicycling infrastructure, particularly among individuals who are most reluctant to ride (McNeil, Monsere, & Dill, 2015). In this study, meters of protected bicycle lanes were very low, and were completely lacking in the Jefferson County data, yielding low variability in this indicator, perhaps explaining why it was not as strongly associated with the behavior as bicycle lanes in general.…”
Section: Discussionmentioning
confidence: 99%
“…Other types of infrastructure, such as sharrows and bicycle signs, may be insufficient to influence bicycling behavior in a meaningful way. Research suggests that protected bicycle lanes are perceived as the most safe and comfortable type of bicycling infrastructure, particularly among individuals who are most reluctant to ride (McNeil, Monsere, & Dill, 2015). In this study, meters of protected bicycle lanes were very low, and were completely lacking in the Jefferson County data, yielding low variability in this indicator, perhaps explaining why it was not as strongly associated with the behavior as bicycle lanes in general.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the importance of safety perceptions on cycling frequency, usage, and behavior (Willis et al, 2015), different safety perception measures are included in our analysis, although they were not tested intensively in previous research. McNeil et al (2015) studied the comfort perception of four cyclists types on different types of infrastructure. However they found that perceptions of comfort did not matched reality.…”
Section: Built Environmentmentioning
confidence: 99%
“…The typology has been used to quantify potentially latent groups of bicyclists in cities, states, and countries. While the use of typologies to quantify the near-market of bicyclists across large cities and regions has been helpful in informing bike riding strategies, prior studies have not explored whether interest in bike riding varies within these geographies, such as across smaller spatial areas of cities and states (8)(9)(10)(11). The availability and quality of transport infrastructure often varies within cities depending on zoning, distance from the city, topography, socioeconomic status and community demographics (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%